The Influence of Capital Adequacy Ratio, Non-Performing Loan, and Loan to Deposit Ratio on Return on Assets : on State-Owned Enterprise Banks is listed on the Indonesia Stock Exchange for the 2015-2024 Period - Adhitama, Prayoga Tri; Sumawidjaja, Riyandi Nur (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This study examines how CAR, NPL, and LDR influenced ROA of SOE Bank from 2015 to 2024. The study's secondary data was collected from the websites of each bank's financial reports. Hypothesis testing, correlation coefficient analysis, regression analysis, classical assumption testing, and coefficient of determination analysis are examples of statistical analysis procedures. The findings demonstrated that LDR negatively impacts ROA, NPL negatively and significantly impacts ROA, and CAR positively and significantly impacts ROA. All things considered, the ROA of SOE banks that were listed at the time on the IDX was significantly influenced by these three ratios taken together.